Effect of Interactive Computer Software Package on Keyboarding Students Academic Achievement Between Gender in Federal Colleges of Education in North East Nigeria - Abdulmumini, H.; Adamu, Z.; Bello, A. (Kashere Journal of Education, 2021)
Abstract The study investigates the effect of interactive computer software package on keyboarding students’ academic achievement among gender in Federal Colleges of Education in North-East Nigeria. The study had two objectives, two research questions and two null hypotheses. The pretest posttest comparison group design was used. The population of the study was 1748 students that offered keyboarding in two of the Federal Colleges of Education in North-east Nigeria in 2019/2020 academic session. Two intact classes of 43 male, 30 female making 176 students and 62 male, 103 female students were used for the study respectively. The instrument used for data collection were keyboarding pre diagnostic achievement test (KPAT) and keyboarding diagnostic achievement test (KDAT) was designed by the researcher and validated by three experts. The data obtained from pilot study were subjected to statistical analysis using Cronbach Alpha. The instrument had Reliability Coefficient of 0.85 while that of posttest was 0.89. The KDAT were administered to student before the treatment while KDAP were administered after the treatment. Data collected from the two instruments were marked by the researcher using drawn marking scheme. The results of the data were coded in to Statistical Package of Social Sciences (SPSS) software version 25. The SPSS was used analyze Descriptive statistics of Mean, Standard Deviation and t-test, Mean and Standard Deviation were used to answer the research question while t-test was employed in testing the null hypotheses at 0.05 level of significance. The result revealed among others that those taught using conventional method perform woefully in both gender. Based on the findings, the researcher concluded that the use of interactive computer software package would help both male and female students to have proficiency in mastering the keyboard which will facilitate their typing skills. It was recommended among others that school should charge all the keyboarding lecturers to use computer software package in teaching the students irrespective of gender.